2022
DOI: 10.1002/jcsm.13043
|View full text |Cite
|
Sign up to set email alerts
|

Myonuclear permanence in skeletal muscle memory: a systematic review and meta‐analysis of human and animal studies

Abstract: One aspect of skeletal muscle memory is the ability of a previously trained muscle to hypertrophy more rapidly following a period of detraining. Although the molecular basis of muscle memory remains to be fully elucidated, one potential mechanism thought to mediate muscle memory is the permanent retention of myonuclei acquired during the initial phase of hypertrophic growth. However, myonuclear permanence is debated and would benefit from a meta-analysis to clarify the current state of the field for this impor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 99 publications
(437 reference statements)
0
9
0
Order By: Relevance
“…While some studies reported that myonuclei were eliminated [ 50 , 51 ], others suggested they were not lost [ 52 , 53 ]. Some studies have pointed out that the discrepancies may be attributed to multiple factors, such as variations in experimental models, limited number of studies, and differences in research design [ 54 ]. It is important to note that the maintenance of quantity of myonuclei requires a balance between their production and apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…While some studies reported that myonuclei were eliminated [ 50 , 51 ], others suggested they were not lost [ 52 , 53 ]. Some studies have pointed out that the discrepancies may be attributed to multiple factors, such as variations in experimental models, limited number of studies, and differences in research design [ 54 ]. It is important to note that the maintenance of quantity of myonuclei requires a balance between their production and apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…The quality of the cohort studies (retrospective or prospective) was assessed using the Newcastle-Ottawa Scale, which specifically included study population selection, comparability, and exposure evaluation or outcome evaluation. The RCTs were conducted for the risk assessment according to the “risk assessment tool” recommended by the Cochrane Collaboration Network[ 18 - 20 ].…”
Section: Methodsmentioning
confidence: 99%
“… 81 In humans, a 1999 study compared the muscle physiology of powerlifters who were users ( n = 9) and non-users of high-dose steroids ( n = 10) and found that the number of myonuclei and the proportion of myonuclei were significantly higher in the steroid users. 80 However, the concept of muscle memory has mainly been based on animal models, with a recent comprehensive review 82 and systematic review and meta-analysis 83 finding no clear evidence for the existence of muscle memory by myonuclei retention in both animal and human studies. In particular, it appears that ‘muscle memory’ is a phenomenon that is not observed in many studies or not retained long term, with many studies, 82 , 83 and it could be debated that any memory marks altered during previous training would be easily modified or overridden by changes in sex hormone concentrations and the subsequent systematic effects of GAHT.…”
Section: Effects Of Gaht On Muscle Strengthmentioning
confidence: 99%
“… 80 However, the concept of muscle memory has mainly been based on animal models, with a recent comprehensive review 82 and systematic review and meta-analysis 83 finding no clear evidence for the existence of muscle memory by myonuclei retention in both animal and human studies. In particular, it appears that ‘muscle memory’ is a phenomenon that is not observed in many studies or not retained long term, with many studies, 82 , 83 and it could be debated that any memory marks altered during previous training would be easily modified or overridden by changes in sex hormone concentrations and the subsequent systematic effects of GAHT. Further research exploring physiological and epigenetic changes in trans men and women using GAHT could provide great molecular insights into the performance differences between cis and trans populations and is an area of future need.…”
Section: Effects Of Gaht On Muscle Strengthmentioning
confidence: 99%